The Promise of Dolutegravir: A Novel Second Generation Integrase Strand Transfer Inhibitor - Singh, Harmanjit; Kaur, Mandeep; K. Kakkar, Ashish; Kumar, Harish (Current Clinical Pharmacology, 2016)
Dolutegravir (DTG), a novel integrase strand transfer inhibitor (INSTI), is one of the newest addition to the arsenal of anti-human immunodeficiency virus (HIV) therapeutics. Dolutegravir is the first member of the class of second generation integrase strand transfer inhibitors aimed primarily to address the current unmet need for novel unboosted integrase inhibitors with convenient once-daily dosing and a superior resistance profile. During its clinical development, DTG has demonstrated noninferior or superior efficacy in both treatment-naive as well as treatmentexperienced individuals including those who have previously failed first generation INSTIs. Other potential advantages include a favorable safety profile, low propensity for drug-drug interactions, and prolonged serum half-life permitting once-daily administration in treatment-naive or treatment-experienced INSTI naive HIV patients. Twice-daily administration is recommended in individuals with established or suspected resistance to first-generation INSTIs. This review outlines the need for new HIV therapeutics and summarizes the efficacy, safety, and pharmacokinetic profile of dolutegravir.
Keywords: integrase strand transfer inhibitor